Under-the-Flap Crosslinking and LASIK in Early Ectasia with Hyperopic Refractive Error - Sylvain el-Khoury; Youssef Abdelmassih; Mazen Amro; Elias Chelala; Elias Jarade (Journal of Ophthalmology)
Purpose. To present safety, efficacy, and early results of a new combinational treatment for early corneal ectasia with hyperopic refractive error aimed to reinstate emmetropia and stabilize cornea. Method. This is a retrospective case series. All surgeries were performed at the Beirut Eye Specialist Hospital, Lebanon. Surgical procedure consisted of (1) lifting flap (post-LASIK ectasia)/creation of corneal flap (keratoconus), (2) application of excimer laser ablation to correct refractive error, (3) loose repositioning of flap, (4) under-the-flap irrigation with riboflavin 0.1% dextran solution, and (5) application of UVA light. Results. A total of 7 eyes (4 patients; mean age 24.25 years; all male) were included. 2 patients had early keratoconus, and 2 patients had early post-LASIK ectasia. Pretreatment vs. last postoperative follow-up visit (mean 11.25 months; range 6–15 months) UDVA (logMAR), spherical equivalent (SE) (D), astigmatism (D), and central pachymetry (µm) were 0.35 ± 0.18 vs. 0.05 ± 0.07, p=0.017; −0.81 ± 0.67 vs. −0.46 ± 0.57, p=0.078; 2.46 ± 0.53 vs. 0.68 ± 0.28, p=0.018; and 547 ± 58 vs. 536 ± 49, p=0.07, respectively. In all eyes, BCVA was 0.1 logMAR or better before and after treatment. No eye showed a decrease in BCVA. Two eyes of one patient had an epithelial ingrowth, which was removed in one case. Follow-up results showed no major complications and no progression of corneal ectasia. Conclusion. Early results showed that under-the-flap CXL with excimer laser correction is an effective treatment for early hyperopic keratectasia, with the advantage of rapid recovery, postoperative corneal stability, and no epithelial healing complications. The procedure seems to bear a risk for postoperative epithelial growth into the flap interface.